Metabolic Fingerprint Analysis of Cytochrome b5-producing E. coli N4830-1 Using FT-IR Spectroscopy - Tengsuttiwat, Thanyaporn; Kaderbhai, Naheed Nazly; Gallagher, Joe; Goodacre, Royston; Muhamadali, Howbeer (Frontiers in Microbiology, 2022)
Optimisation of recombinant protein expression in bacteria is an important task in order to increase protein yield while maintaining structural fidelity of the product. In this study we employ Fourier transform infrared (FT-IR) spectroscopy as a high throughput metabolic fingerprinting approach to optimise and monitor cytochrome b5 (CYT b5) production in Escherichia coli N4830-1, as the heterologous host. Cyt b5 was introduced as a plasmid with between 0-6 copies under a strong promoter. The FT-IR spectroscopy results combined with multivariate chemometric analysis illustrated discriminations among culture conditions as well as revealing features that correlated to the different cyt b5 gene copy numbers. The second derivative of the FT-IR spectral data allowed for the quantitative detection of CYT b5 directly inside the intact cells without the need for extraction, and highlighted changes in protein secondary structure that was directly correlated to the cyt b5 gene copy number and protein content, and was in complete agreement with quantitative findings of standard traditional techniques such as SDS-PAGE and western blot analysis.